2009
DOI: 10.1177/0269881108100255
|View full text |Cite
|
Sign up to set email alerts
|

NK1 (TACR1) receptor gene ‘knockout’ mouse phenotype predicts genetic association with ADHD

Abstract: Mice with functional genetic ablation of the Tacr1 (substance P-preferring receptor) gene (NK1R−/−) are hyperactive. Here, we investigated whether this is mimicked by NK1R antagonism and whether dopaminergic transmission is disrupted in brain regions that govern motor performance. The locomotor activity of NK1R−/− and wild-type mice was compared after treatment with an NK1R antagonist and/or psychostimulant (d-amphetamine or methylphenidate). The inactivation of NK1R (by gene mutation or receptor antagonism) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 67 publications
(92 reference statements)
5
63
1
Order By: Relevance
“…Regulation of dopaminergic, noradrenergic and serotonergic transmission in corticostriatal brain regions is also disrupted in these mutant mice (Froger et al, 2001;Herpfer et al, 2005;Yan et al, 2011), as is thought to be the case in ADHD. Our proposal that NK1R-/-mice express the key signs of this disorder is supported by evidence for an association between polymorphisms in, or near, the TACR1 receptor gene (the human equivalent of the nk1R gene) and increased vulnerability to ADHD (Yan et al, 2010).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Regulation of dopaminergic, noradrenergic and serotonergic transmission in corticostriatal brain regions is also disrupted in these mutant mice (Froger et al, 2001;Herpfer et al, 2005;Yan et al, 2011), as is thought to be the case in ADHD. Our proposal that NK1R-/-mice express the key signs of this disorder is supported by evidence for an association between polymorphisms in, or near, the TACR1 receptor gene (the human equivalent of the nk1R gene) and increased vulnerability to ADHD (Yan et al, 2010).…”
Section: Introductionmentioning
confidence: 61%
“…Spontaneous mutation(s) in wild type and/or NK1R-/-mice are also possible. Nevertheless, acute antagonism of NK1R does increase locomotor activity of the wild types (Yan et al, 2010) and so this behaviour, at least, is not affected by such confounding influences. Similarly, premature responses after treatment with L-5 were greater than after L-10, and lower after RP-10 than RP-5 in both wild types tested in the morning and NK1R-/-mice tested in the afternoon.…”
Section: Nk1r Antagonists Disrupt Behaviour Of Wild Type and Nk1r-/-mmentioning
confidence: 98%
“…Deletion of some of these genes in animals (e.g. SNAP25, TACR1) results in phenotypes suggesting a strong association with some of the ADHD symptoms (Mill et al 2004;Yan et al 2010). However, none of the genes implicated have been shown to be solely responsible for the complex behavioural pattern in ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the limited construct validity and the ambiguous face and predictive validity of these mutants significantly question the use of these mice as a putative ADHD model. Recent preliminary investigations have suggested that the mice deficient in NK1 receptor (Yan et al 2010) and steroid sulfatase ) might be also relevant for ADHD, but a very limited information available at present prevents from the unambiguous categorization of these mice as putative models of ADHD.…”
Section: Other Genetic Models Of Adhdmentioning
confidence: 99%